Children's food choices: Health risks and impacts on adult life - Santo, Lohayne Marins do Espírito; Alves, Claudia Maria Fiuza; Martinelli, Lucas; Barbosa, Brunno Machado; Santos, Vinicius Teixeira; Marcussi, Bernardo Alberto; Corado, Patrícia Ribeiro; Marcussi, Adriana Paula Slongo (Seven Editora, 2023)
Nowadays, time has become a scarce wealth in the face of the countless tasks to be fulfilled. Within this reality, practicality has become overvalued. This is when habits such as the consumption of processed foods emerge, which compared to fresh  foods require less preparation time. For their commercialization, these foods are packaged in packaging used as merchandising space, bringing implicit and explicit information that often associates them with happiness and well-being. However, the idea constructed by marketing may not be consistent with the real meaning of food for health. All foods have nutritional information on their labels, where this may be the only source of information available to the consumer at the time of purchase, so it is essential that the consumer is able to understand and use the available information. The fact that labeling is mandatory does not mean that consumers are using it as a tool for choosing healthy foods, which makes the food industry take advantage of this and invest in eye-catching packaging. The objective of this study was to analyze the packaging of some industrialized products generally consumed by children, in order to allow a greater reflection and more conscious and correct choices regarding children's health. For this analysis, the following products were selected: nesfit – cocoa and cereals, chocolate trakinas and Ana Maria vanilla flavored cupcake. The analyses were carried out on the labels of the products, as well as the ingredients and according to their nutritional table. It can be seen from the analysis of these products widely consumed by children, that the great increase in obese children and with problems of increased blood pressure, is due to an unbalanced diet, allowed by the parents themselves since they do not pay attention to the labeling of children's products that are full of sugars, trans fat and sodium as can be seen in the products analyzed.  and that are widely consumed by children, which causes a taste linked to foods, especially rich in carbohydrates and additives introduced in the form of salt, causing risks of childhood obesity and increased blood pressure in adulthood. DOI:https://doi.org/10.56238/sevened2023.006-036